Proton and Electron Temperatures in the Solar Wind and Their Correlations with the Solar Wind Speed - Chen Shi; Marco Velli; Roberto Lionello; Nikos Sioulas; Zesen Huang; Jasper S. Halekas; Anna Tenerani; Victor Réville; Jean-Baptiste Dakeyo; Milan Maksimović; Stuart D. Bale (The Astrophysical Journal, 2023)
The heating and acceleration of the solar wind remains one of the unsolved fundamental problems in heliophysics. It is usually observed that the proton temperature T _i is highly correlated with the solar wind speed V _SW , while the electron temperature T _e shows anticorrelation or no clear correlation with the solar wind speed. Here, we inspect both Parker Solar Probe (PSP) and WIND data, and compare the observations with simulation results. PSP observations below 30 solar radii clearly show a positive correlation between the proton temperature and the wind speed and a negative correlation between the electron temperature and the wind speed. One year (2019) of WIND data confirm that the proton temperature is positively correlated with the solar wind speed, but the electron temperature increases with the solar wind speed for slow wind, while it decreases with the solar wind speed for fast wind. Using a 1D Alfvén-wave-driven solar wind model with different proton and electron temperatures, we find, for the first time, that if most of the dissipated Alfvén wave energy heats the ions instead of the electrons, a positive T _i – V _SW correlation and a negative T _e – V _SW correlation arise naturally. If the electrons gain a small but finite portion of the dissipated wave energy, the T _e – V _SW correlation evolves with the radial distance to the Sun, such that the negative correlation gradually turns positive. The model results show that Alfvén waves are one of the possible explanations for the observed evolution of the proton and electron temperatures in the solar wind.